2001
DOI: 10.1136/bmj.323.7325.1331
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and early life growth and body mass index from birth to early adulthood in 1958 British cohort: longitudinal study

Abstract: Objectives To determine the influence of birth weight on body mass index at different stages of later life; whether this relation persists after accounting for potential confounding factors; and the role of indicators of fetal growth (birth weight relative to parental size) and childhood growth. Design Longitudinal study of the 1958 British birth cohort. Setting England, Scotland, and Wales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
348
6
17

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(388 citation statements)
references
References 16 publications
14
348
6
17
Order By: Relevance
“…Also weight was classified by the ponderal index, calculated as {[birth weight (g)]/length (cm)] 3 } 3 100, and categorized as follows: low (#2?49); normal (2?50-3?16); and high ($3?17) (24) . Gestational age was classified as: pre-term (,37 weeks' gestation, under 259 d); full-term (37-41 weeks' gestation, 259-293 d); and post-term ($42 weeks' gestation, 294 d or more).…”
Section: Methodsmentioning
confidence: 99%
“…Also weight was classified by the ponderal index, calculated as {[birth weight (g)]/length (cm)] 3 } 3 100, and categorized as follows: low (#2?49); normal (2?50-3?16); and high ($3?17) (24) . Gestational age was classified as: pre-term (,37 weeks' gestation, under 259 d); full-term (37-41 weeks' gestation, 259-293 d); and post-term ($42 weeks' gestation, 294 d or more).…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Whitaker, 9 American children with a large birth weight (X90th percentile) had the higher percentages of obese children at 2-4 years of age, which is more apparent in boys than that in girls. A longitudinal study by Parsons et al 10 indicated that the association between higher birth weight and higher levels of BMI may persist into adulthood among the participants of a British birth cohort. In our study, the association between prenatal and postnatal development at 1-3 years of age was attenuated after controlling for postnatal illness status and feeding modalities.…”
Section: Macrosomia and High Weight-for-height Z Yu Et Almentioning
confidence: 99%
“…Gestational age of our study subjects was not included in this analysis, as the duration of gestation does not seem to have any influence on later infant body weight. 10 Because data was collected at the first postpartum month, the data of maternal prenatal or preconception anthropometric measurements was not available for the current analyses. Maternal prenatal body weight Macrosomia and high weight-for-height Z Yu et al and weight gain was previously reported to influence children's body weight.…”
Section: Macrosomia and High Weight-for-height Z Yu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…20 Studies on the association between fetal macrosomia and obesity in childhood, adolescence, and adulthood, mostly conducted in industrialized countries, have yielded inconsistent findings. [21][22][23][24][25][26][27] The objective of this study was to examine the association between macrosomia at birth and subsequent obesity in adolescence in a rural population in China.…”
Section: Introductionmentioning
confidence: 99%